CRY2 mediates the cognitive decline induced by sleep deprivation in 5xFAD mice - Luo, Sumei; Guo, Lizhe; Chen, Na; Guo, Qulian; Xie, Yongqiu; Wang, Yunjiao; Wang, E. (PLOS ONE, 2024)
Background Cryptochrome-2 (CRY2) is a core rhythm gene that plays a crucial role in DNA damage repair. The present study investigated the potential role of CRY2 in mediating sleep deprivation-induced cognitive decline in 5xFAD mice. Methods To assess the effects of SD on different brain regions of the mouse brain, we used 18F FDG PET-CT. Cognitive function was evaluated using the Morris water maze test and Y-maze. Lentivirus was used for the overexpression of CRY2, and small interfering RNA (siRNA) was used for the downregulation of CRY2 to verify the effect of CRY2. We used qRT‒PCR and Western blotting to identify the downstream factors of CRY2 and evaluated the cognitive function of mice to confirm the effects of these factors. Results The AD mice exhibited cognitive decline after 21 days of SD and had higher expression of CRY2 compared to AD mice with normal sleep. Overexpression of CRY2 led to decreased cognitive function in AD mice, and the downregulation of CRY2 attenuated the SD-induced cognitive decline in AD mice. CRY2 reduced the expression and function of CISH, which reduced the inhibition of STAT1 phosphorylation and led to synaptic dysfunction. CISH overexpression attenuated the impairing effect of sleep deprivation on cognitive function in AD mice. Furthermore, 18F FDG PET-CT revealed that SD significantly reduced glucose metabolism in different brain regions of AD mice. Conclusion Our study demonstrated that sleep deprivation upregulated CRY2 in the hippocampus of AD mice, which resulted in synaptic dysfunction by decreasing CISH-mediated STAT1 phosphorylation.